Antigammaglobulin antibodies in rheumatic fever - Bilir, Servet; Armaç, Aysel (The Turkish Journal of Pediatrics, 1973)
In Dr. Sami Ulus Children's Hospital twenty-two patients between the ages of four eleven year with a characteristic picture of rheumatic fever were studied for the presence of anti-gammaglobulin antibodies. In seventeen out of twenty-two (77,1%) the latex-fixation test gave positive results. Fourteen of these patients had active rheumatic heart disease (82,9%). The significance and the frequency of these antibodies rheumatic fever is discussed.